RESILIENSI AKADEMIK DAN ACADEMIC SELF-EFFICACY PADA MAHASISWA CAREGIVER KELUARGA DEMENSIA - Dede Kristin; Rahmah Hastuti (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Students who care for family members with dementia face dual demands in the form of academic responsibilities and caregiving duties, which may increase stress and interfere with academic functioning. This study aimed to examine the relationship between academic resilience and academic self-efficacy among student caregivers of family members with dementia. This study employed a quantitative correlational design involving 158 active university students who served as family caregivers and were selected using purposive sampling. Data were collected using an academic resilience scale and an academic self-efficacy scale, and were analyzed using Spearman’s correlation test. The results showed a significant positive relationship between academic resilience and academic self-efficacy (ρ = 0.725; p < 0.001). These findings indicate that the higher the students’ academic resilience, the higher their confidence in their ability to manage academic demands while carrying out caregiving roles. This study extends the empirical understanding of the psychological dynamics of student caregivers of family members with dementia and highlights the importance of psychological support and more responsive university policies to address their needs. ABSTRAK Mahasiswa yang merawat anggota keluarga dengan demensia menghadapi tuntutan ganda berupa kewajiban akademik dan tanggung jawab caregiving, yang dapat meningkatkan stres dan mengganggu fungsi akademik. Penelitian ini bertujuan untuk menganalisis hubungan antara resiliensi akademik dan academic self-efficacy pada mahasiswa caregiver keluarga penyandang demensia. Penelitian ini menggunakan desain kuantitatif korelasional dengan melibatkan 158 mahasiswa aktif yang berperan sebagai caregiver keluarga, yang dipilih melalui teknik purposive sampling. Data dikumpulkan menggunakan skala resiliensi akademik dan skala academic self-efficacy, kemudian dianalisis dengan uji korelasi Spearman. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara resiliensi akademik dan academic self-efficacy (ρ = 0,725; p < 0,001). Temuan ini menunjukkan bahwa semakin tinggi resiliensi akademik, semakin tinggi pula keyakinan mahasiswa terhadap kemampuannya dalam menyelesaikan tuntutan akademik di tengah peran caregiving. Studi ini memperluas pemahaman empiris mengenai dinamika psikologis mahasiswa caregiver keluarga penyandang demensia serta menegaskan pentingnya dukungan psikologis dan kebijakan kampus yang lebih responsif terhadap kebutuhan mereka.